2022
DOI: 10.3389/fonc.2022.941079
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory system toxicity induced by immune checkpoint inhibitors: A real-world study based on the FDA adverse event reporting system database

Abstract: BackgroundImmune checkpoint inhibitors (ICIs), the treatment of multiple cancer types, can be associated with respiratory system adverse events (AEs). The aim of this study is to quantify the association of respiratory system AEs and ICIs and to characterize the profiles of ICI-related respiratory system complications from Food and Drug Administration Adverse Event Reporting System (FAERS) data.MethodsThe disproportionality of respiratory system AE-related ICIs based on FAERS data from January 2014 to Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Interstitial lung diseases and pneumonia were significantly associated with all ICIs. In addition, 7 of the 10 specific respiratory AEs (lower respiratory tract disease, pleural disease, pulmonary vascular disease, unclassified respiratory disease (NEC), respiratory infection, respiratory tumor, and chest disease) are associated with ICIs ( 117 ).…”
Section: Common Iraesmentioning
confidence: 99%
“…Interstitial lung diseases and pneumonia were significantly associated with all ICIs. In addition, 7 of the 10 specific respiratory AEs (lower respiratory tract disease, pleural disease, pulmonary vascular disease, unclassified respiratory disease (NEC), respiratory infection, respiratory tumor, and chest disease) are associated with ICIs ( 117 ).…”
Section: Common Iraesmentioning
confidence: 99%
“…First, we compared ICI regimens with high-frequency AEs reported from the whole database. ICI treatment strategies are associated Frontiers in Pharmacology frontiersin.org with a high incidence of toxicity in multiple organ systems, which are not limited to hematologic and lymphatic systems but also include the endocrine (Zhai et al, 2019), respiratory (Cui et al, 2022), hepatic (Remash et al, 2021), and renal systems (Hu et al, 2021). In our study, hematologic and lymphatic AEs were reported more frequently in patients treated with anti-PD-1/PD-L1 monotherapy than in those treated with anti-CTLA-4 monotherapy, with atezolizumab showing the strongest risk signal.…”
Section: Figurementioning
confidence: 99%
“…The analysis of spontaneous reporting databases, such as the FDA Adverse Even Reporting System (FAERS) and WHO Vigibase, allows a broader perspective by collecting unpublished reports of adverse events submitted all over the world occurring in real-world unselected subjects with comorbidities, poly-pharmacotherapy and complex anticancer combination regimens ( Raschi et al, 2020 ), which ensures rapid detection of even rare adverse events. Previous disproportionality analysis based on the FAERS database indicated that interstitial lung disease ( Guo et al, 2023 ), pulmonary tuberculosis ( Zhu et al, 2022a ) and pneumonitis ( Cui et al, 2022 ) were found to be significantly associated with ICIs exposure. But it is still unclear if ICIs were associated with increased reporting frequency of PJP in the real-world clinical setting.…”
Section: Introductionmentioning
confidence: 99%